Excel Crash Course for Engineers - Hossain, Eklas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
Excel Crash Course for Engineers is a reader-friendly introductory guide to the features, functions, and applications of Microsoft Excel in engineering. The book provides readers with real-world examples and exercises that are directly related to engineering, and offers highly illustrated, step-by-step demonstrations of techniques to solve and visualize engineering problems and situations. The book includes an introduction to MS Excel, along with in-depth coverage of graphing and charting, functions and formulae, Excel's Visual Basic for Applications (VBA) programming language, and engineering data analysis. This powerful tutorial is a great resource for students, engineers, and other busy technical professionals who need to quickly acquire a solid understanding of Excel. Concise guide to engineering with Excel; Examples and exercises directly related to engineering; Offers highly illustrated, step-by-step guidance.
Introduction to Microsoft Excel -- Graphing and Charting -- Functions and Formulae -- Visual Basic for Applications (VBA) -- Engineering Data and Analysis.
Keywords: Engineering mathematics; Engineering$1 (BData processing.s; Engineering design; Microsoft software; Microsoft .NET Framework; Mathematical and Computational Engineering Applications; Engineering Design; Microsoft; Data Engineering